2022
DOI: 10.1021/acssuschemeng.2c01864
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Alginate-Promoted Soil Phosphorus Availability

Abstract: Phosphorus (P) is a nonrenewable resource with low availability in soils and thus can be a yield-limiting factor for food production. Alginate from brown algae has been proved to be a promising fertilizer additive to promote P utilization efficiency so as to achieve sustainable P management. However, there has been a lack of direct observation of how alginate promotes P availability due to the complexity of the soil system. Here, by combining in situ atomic force microscopy (AFM) and Raman spectroscopy, we in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…An efficient dissolution ability of Fe and P by organic acids may be attributed to the fact that the dissociation of protons from carboxyl groups promotes bond breaking, thus leading to mineral dissolution. , The carboxyl group has the ability to chelate metals as ligands, and its metal chelation ability increases with the increasing number of carboxyl groups. Studies have indicated that proton-promoted mineral dissolution results from the exchange action between H + and cations on mineral surfaces and the hydrolysis action of metal–O bonds under acidic conditions. Organic ligands can form surface complexes with metal ions, thus decreasing the energy barrier of mineral hydrolysis reactions, eventually promoting mineral dissolution. It is through this mechanism that citric acid dissolves inorganic P minerals. ,, Additionally, alginate acid dissolved inorganic Fe–P precipitates by different mechanisms at various solution-pH-induced H + concentrations and −COOH dissociation states . Under acidic conditions, the dissolution of Fe–P minerals is driven by both H + and −COO – in the solution, while under neutral or alkaline conditions, the dissolution of Fe–P precipitates is promoted only by −COO – …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An efficient dissolution ability of Fe and P by organic acids may be attributed to the fact that the dissociation of protons from carboxyl groups promotes bond breaking, thus leading to mineral dissolution. , The carboxyl group has the ability to chelate metals as ligands, and its metal chelation ability increases with the increasing number of carboxyl groups. Studies have indicated that proton-promoted mineral dissolution results from the exchange action between H + and cations on mineral surfaces and the hydrolysis action of metal–O bonds under acidic conditions. Organic ligands can form surface complexes with metal ions, thus decreasing the energy barrier of mineral hydrolysis reactions, eventually promoting mineral dissolution. It is through this mechanism that citric acid dissolves inorganic P minerals. ,, Additionally, alginate acid dissolved inorganic Fe–P precipitates by different mechanisms at various solution-pH-induced H + concentrations and −COOH dissociation states . Under acidic conditions, the dissolution of Fe–P minerals is driven by both H + and −COO – in the solution, while under neutral or alkaline conditions, the dissolution of Fe–P precipitates is promoted only by −COO – …”
Section: Introductionmentioning
confidence: 99%
“…5,31,32 Additionally, alginate acid dissolved inorganic Fe−P precipitates by different mechanisms at various solution-pH-induced H + concentrations and −COOH dissociation states. 33 Under acidic conditions, the dissolution of Fe−P minerals is driven by both H + and −COO − in the solution, while under neutral or alkaline conditions, the dissolution of Fe−P precipitates is promoted only by −COO − . 34 It has been reported that organic acids such as oxalic acid and citric acid can release P by dissolving inorganic Fe−P precipitates in a pH-dependent manner, 22,35,36 but there exist some controversies about the role of H + in mineral dissolution.…”
Section: Introductionmentioning
confidence: 99%